(untitled) (Proceeding of the International Conference on Arts and Humanities, 2019)
This research was conducted to measure the streetscape complexity created by streetscape signage. Four objective analysis techniques; Shannon entropy, Simpson Index, Gini Coefficient, Fractal Dimension analysis and human visual perception (subjective measurement) were used as the measurement tools of visual complexity created by streetscape signage. The perspective views of hundred urban streetscapes with commercial and public signage from the Colombo Municipal Council area were displayed to a group of subjects and their perception of the complexity due to signage was identified. Meanwhile, the objective measurements were undertaken. The variety and the number of streetscape signage available along either side of the streetscapes were used for the Shannon entropy and the Simpson index calculations. The number of visual elements available in each signage along the streetscapes was used for Gini Coefficient calculations while the monochrome perspective views were applied for the Fractal Dimension analysis using the Fractalyse software. Finally, the results of the subjects’ perception and the objective analysis methods were compared. According to the comparisons, the result of the Gini coefficient was more equivalent with the human perception. While the Shannon entropy and the Simpson Index calculations showed minor deviations, and the result of the fractal dimension analysis was not compatible with the human perception.